Evaluating attention deficit and hyperactivity disorder (ADHD): a review of current methods and issues - Musullulu, Hande (Frontiers in Psychology, 2025)
Attention-deficit/hyperactivity disorder (ADHD) is a common and complex neurodevelopmental disorder that affects individuals across the lifespan. This review provides an overview of the DSM diagnostic criteria for ADHD and discusses recommended considerations for the diagnosis of ADHD in children, adolescents, and adults. Its complexity requires careful consideration in the diagnostic process due to heterogeneity in clinical presentation and symptom overlap with other conditions. Commonly used assessment tools, including clinical interviews, rating scales and continuous performance tasks are reviewed with a focus on their psychometric qualities. Limitations of current diagnostic techniques, including issues related to gender bias, comorbidities and the importance of differential diagnosis are also reviewed. Improvements in the consistency and accuracy of ADHD diagnosis may be achieved by addressing these factors and evaluating the practical application of diagnostic tools.